ANALISIS BIAYA DAN EFEKTIVITAS TERAPI PASIEN DIABETES MELITUS TIPE 2 RAWAT JALAN DI RSUD SLEMAN YOGYAKARTA - , pratiwi dinaryanti, Prof. Dr. Achmad Fudholi, DEA., Apt ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Diabetes is a chronical disease that can significantly increase someoneâs risk of having complications. These complications are not only cause the inability of the body that will affect the quality of life, but also need the big cost. This research was conducted to analyze the costs and effectiveness of therapies of outpatient with type 2 diabetes mellitus. A crosssectional observational method was performed on patient who were admitted to the Department of Endocrinology of the Sleman Hospital between December 2010zzxvvh to January 2011. The data were taken in 2 ways: concurrent and retrospective, with accidental sampling technique. The Subject of this research are out patient with type 2 diabetes mellitus at RSUD Sleman Yogyakarta, who have used the antidiabetic therapy for at least three months of therapy before the quality of life measurement. The Costs that are measured are direct medical costs, antidiabetic costs, complication costs, laboratory examination costs, and administration costs. The effectiveness of treatment parameters is measured based on the percentage of patients with fasting blood glucose level (GDP) and post-prandial blood glucose (GDPP) which reached the target in the third month of therapy, and achievement of the quality of life research subjects. The Lowest total cost of therapy is on the use of glibenclamide, it was Rp. 49.730,00, the highest total cost of therapy is on the use of insulin, it was Rp 411.045,50. T test results with 95% confidence level indicates that the patient characteristics and medication adherence complications affect the quality of life of patients, whereas non-pharmacological therapy (exercise and diet) did not significantly influence the quality of life of patients. The results of measurements of quality of life showed metformin achieved the best quality of life than the other antidiabetic, it was 72.53. Based on the effectiveness of the three parameters (measurement of quality of life and levels of GDP and GDPP) is noted that metformin therapy tend to be more effective compared with other antidiabetic therapies.